Clinical Characteristics of Fulminant Type 1 Diabetes Compared with Typical Type 1 Diabetes: One-Year Follow-Up Study from the Guangdong T1DM Translational Medicine Study - Daizhi Yang; Yongwen Zhou; Sihui Luo; Xueying Zheng; Ping Ling; Liling Qiu; Wen Xu; Hua Liang; Bin Yao; Jianping Weng; Jinhua Yan (Journal of Diabetes Research)
Background. Fulminant type l diabetes mellitus (FT1DM) is a subtype of type 1 diabetes mellitus (T1DM) with abrupt onset, but data on its progression was limited. This study was aimed at exploring the clinical features through one-year follow-up. Methods and Materials. Patients with T1DM finishing at least one-year follow-up from June 2011 to July 2018 were enrolled from Guangdong Type 1 Diabetes Translational Medicine Study. Patients who fulfilled the respective criteria were categorized as an FT1DM group and a typical T1DM group (TT1DM). The 1 : 4 propensity score matching based on onset age, duration, and gender was performed between the FT1DM and TT1DM groups. Characteristics at the onset and after one-year follow-up were compared between the two groups. Results. A total of 53 patients with FT1DM and 212 matched patients with TT1DM were included. At the onset, there was a shorter duration of symptomatic period before diagnosis observed in the FT1DM group than in the TT1DM group (2 [1, 7] vs. 30 [10, 60] days, P<0.001). FT1DM patients had higher plasma glucose levels and higher percentage of diabetes ketoacidosis (P<0.001, respectively). Both fasting and postprandial C-peptide levels (FCP and PCP, respectively) in FT1DM were significantly lower (P<0.001). At enrollment, the duration of diabetes was 0.03 (0.00, 0.81) and 0.07 (0.00, 1.11) years and the level of HbA1c was 7.21±1.56% and 10.06±3.23% (P<0.001) in the FT1DM and TT1DM groups, respectively. After one year, both FCP and PCP were still significantly lower in the FT1DM group (P<0.001, 0.022) and the HbA1c level was similar between the two groups (P=0.128). The level of HDL-C in FT1DM was significantly higher than that in the TT1DM group at enrollment (P=0.019), and the change from enrollment was significantly greater than that in the FT1DM group (P=0.042). Conclusion. Patients with FT1DM had more severe metabolic derangement and deficiency of insulin secretion than patients with TT1DM at the onset, but glycaemic and metabolic control was not worse than that in TT1DM.